Aerobic decolorization and detoxification of Acid Scarlet GR by a newly isolated salt-tolerant yeast strain Galactomyces geotrichum GG. (November 2019) - Guo, Guang; Tian, Fang; Zhao, Yanhong; Tang, Maomao; Liu, Weijie; Liu, Cong; Xue, Shuwen; Kong, Weina; Sun, Yanmei; Wang, Shiwei
Abstract: Azo dyes are huge social and environmental hazards. Selective fungi are potential degraders for azo dyes and are of great significance to cleaning up and bioremediation. In this study, a salt-tolerant yeast strain GG with the ability to aerobically degrade and detoxify various azo dyes was isolated and identified as Galactomyces geotrichum . The optimal growth and decolorization parameters of strain GG were 0.1 g/L of yeast extract, 2.0 g/L of glucose, 0.4 g/L of ammonium sulfate, ≤ 40 g/L of NaCl, and pH values of 7.0–8.0. Under the optimal condition more than 92% of 100 mg/L of Acid Scarlet GR could be decolorized within 10 h by degradation, which was further confirmed by Fourier transform infrared spectroscopy. In addition, enzymatic analysis showed that the reductase NADH-DCIP and two oxidoreductases lignin peroxidase and laccase played the key roles in the degradation of Acid Scarlet GR, and the decolorization metabolites of Acid Scarlet GR exhibited much less toxicity than the parent dye by phytotoxicity assessment. The results improved the knowledge of azo-dye-decolorizing G. geotrichum species and provided efficient fungal resource for treatment of industrial wastewater containing azo dyes and salts. Highlights: A salt-tolerant yeast Galactomyces geotrichum GG decolorized various azo dyes. Acid Scarlet GR was detoxified effectively by G. geotrichum GG. The responsive enzymes of G. geotrichum GG for degradation were analyzed. Phytotoxicity of decolorization metabolites was evaluated.